Community curation of bioinformatics software and data resources - Ison, Jon; Ménager, Hervé; Brancotte, Bryan; Jaaniso, Erik; Salumets, Ahto; Raček, Tomáš; Lamprecht, Anna-Lena; Palmblad, Magnus; Kalaš, Matúš; Chmura, Piotr; Hancock, John M; Schwämmle, Veit; et al. (Briefings in bioinformatics, 2020)
The corpus of bioinformatics resources is huge and expanding rapidly, presenting life scientists with a growing challenge in selecting tools that fit the desired purpose. To address this, the European Infrastructure for Biological Information is supporting a systematic approach towards a comprehensive registry of tools and databases for all domains of bioinformatics, provided under a single portal (https://bio.tools). We describe here the practical means by which scientific communities, including individual developers and projects, through major service providers and research infrastructures, can describe their own bioinformatics resources and share these via bio.tools.
Keywords: database; systémy řízení databází; Evropa; registry; Europe; software; community driven; Humans; Computational Biology; curation; Software; účast komunity; bioinformatics; Community Participation; výpočetní biologie; lidé; Database Management Systems